Pain assessment in animal models: do we need further studies? - Gigliuto C; De Gregori M; Malafoglia V; Raffaeli W; Compagnone C; Visai L; Petrini P; Avanzini MA; Muscoli C; Viganò J; Calabrese F; Dominioni T; et al. (Journal of Pain Research, 2014)
Carmelo Gigliuto,1 Manuela De Gregori,2 Valentina Malafoglia,3 William Raffaeli,3 Christian Compagnone,4 Livia Visai,5,6 Paola Petrini,7 Maria Antonietta Avanzini,9 Carolina Muscoli,8 Jacopo Viganò,11 Francesco Calabrese,11 Tommaso Dominioni,11 Massimo Allegri,2,10 Lorenzo Cobianchi111Anaesthesia and Intensive Care, University of Pavia, Pavia, 2Pain Therapy Service, Fondazione IRCCS Policlinico San Matteo, Pavia, 3ISAL Foundation, Institute for Research on Pain, Torre Pedrera, Rimini, 4Department of Anaesthesia, Intensive Care and Pain Therapy, Azienda Ospedaliera Universitaria Parma, University of Parma, Parma, 5Department of Molecular Medicine, Center for Tissue Engineering (CIT), INSTM UdR of Pavia, University of Pavia, Pavia, 6Department of Occupational Medicine, Ergonomy and Disability, Laboratory of Nanotechnology, Salvatore Maugeri Foundation, IRCCS, Veruno, 7Dipartimento di Chimica, Materiali e Ingegneria Chimica 'G Natta' and Unità di Ricerca Consorzio INSTM, Politecnico di Milano, Milan, 8Department of Health Science, University Magna Grecia of Catanzaro and Centro del Farmaco, IRCCS San Raffaele Pisana, Roma, 9Laboratory of Transplant Immunology/Cell Factory, Fondazione IRCCS Policlinico "San Matteo", Pavia, 10Department of Clinical, Surgical, Diagnostic and Paediatric Sciences, University of Pavia, Pavia, 11University of Pavia, Department of Surgical, Clinical, Paediatric and Diagnostic Science, General Surgery 1, IRCCS Fondazione Policlinico San Matteo, Pavia, ItalyAbstract: In the last two decades, animal models have become important tools in understanding and treating pain, and in predicting analgesic efficacy. Although rodent models retain a dominant role in the study of pain mechanisms, large animal models may predict human biology and pharmacology in certain pain conditions more accurately. Taking into consideration the anatomical and physiological characteristics common to man and pigs (median body size, digestive apparatus, number, size, distribution and communication of vessels in dermal skin, epidermal–dermal junctions, the immunoreactivity of peptide nerve fibers, distribution of nociceptive and non-nociceptive fiber classes, and changes in axonal excitability), swines seem to provide the most suitable animal model for pain assessment. Locomotor function, clinical signs, and measurements (respiratory rate, heart rate, blood pressure, temperature, electromyography), behavior (bright/quiet, alert, responsive, depressed, unresponsive), plasma concentration of substance P and cortisol, vocalization, lameness, and axon reflex vasodilatation by laser Doppler imaging have been used to assess pain, but none of these evaluations have proved entirely satisfactory. It is necessary to identify new methods for evaluating pain in large animals (particularly pigs), because of their similarities to humans. This could lead to improved assessment of pain and improved analgesic treatment for both humans and laboratory animals.Keywords: pain assessment, experimental model, translational research